Performance Capabilities of a Mobile Laboratory for Supporting Immunological Monitoring in Natural Plague Foci - S. A. Bugorkova; O. M. Kudryavtseva; S. A. Shcherbakova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2024)
Mobile laboratories for implementing anti-epidemic measures in the territories of natural plague foci perform an important function of ensuring sanitary-epidemiological well-being of the country. The aim of the study was to determine the range of areas and tactics for deploying mobile laboratories to ensure the current tasks of immunological monitoring over the health status of the population at risk in the territory of a natural plague focus. Retrospective analysis of the results of long-term immunological monitoring of the risk contingent vaccinated against plague was carried out. The possibilities and prospects for using a mobile laboratory for immunological monitoring within the framework of ensuring the tasks and functions of the Rospotrebnadzor have been determined. Mobile laboratories for immunological monitoring expand the capacities to solve operational issues related to the provision of specific prophylaxis of particularly dangerous infectious diseases, and their deployment as part of other mobile units of the Sanitary-Epidemiological Service will contribute to a more accurate delimitation of the territory, volume, scope and priority of any given preventive measure.